Anchoring of 10-phenylphenothiazine to mesoporous silica materials: A water compatible organic photocatalyst for the degradation of pollutants. (20th March 2022) - González-Muñoz, Daniel; Gómez-Avilés, Almudena; Molina, Carmen B.; Bedia, Jorge; Belver, Carolina; Alemán, Jose; Cabrera, Silvia
Highlights: An organic photocatalyst (PTH) has been anchored onto mesoporous silica-based materials. The PTH-containing materials have been fully characterized by different methods. The photocatalytic activity of the materials has been tested for degradation of pollutants in water. The SBA-15-AP-PTH was the most efficient for degrading acetaminophen and diclofenac. Abstract: The application of organic photocatalysts towards the oxidation of pollutants in water is hampered by different limitations such as their insolubility in the media. Herein, we report that the grafting of a photo-organocatalyst into mesoporous silica materials is an ideal approach to obtain effective catalysts. Thereby, the photocatalyst 10-phenylphenothiazine (PTH) was easily anchored into three different mesoporous silica-based materials (MSN, MSU-2 and SBA-15) with different particle sizes and pore sizes through an amide bond formation. The materials were characterized using IR analysis, solid-state X-ray diffraction, porosity and microscopy (SEM and TEM) techniques, showing that PTH is immobilized inside the pores of the materials and its optical properties are maintained after the anchoring. Although homogeneous PTH was inactive in water media, the three photocatalytic materials were active for the degradation of pollutants. SBA-15-AP-PTH exhibited the highest catalytic performance towards the degradation of acetaminophen and diclofenac under solar irradiation, finding in this manner a new strategy for the decontamination of pollutants. Graphical abstract: Image, graphical abstract